Verso e reverso : práticas sociais, econômicas e políticas no Kongo e no Ndongo e o domínio colonial português - séc. 15 a 17 - Caregnato, Lucas (2012)
This thesis work aims to analyze the social and economic relations, the Bantu village communities that comprised the Ndongo and Kongo in the ages 15 to 17. To understand the political and economic relations of these kingdoms in the period prior to European colonial domination, is a necessary historiographical analysis covering the domestic mode of production, present in these communities. For centuries, these people developed economic practices, rooted in farming, hunting and gathering, which formed the basis for organizing these groups, based on matrilineal or patrilineal parental bonding. With the beginning of Portuguese colonial exploitation by the arrival of Portuguese explorer Diogo Cao in 1482-3 there were profound changes in economic, political and social problems, representing the beginning of a long period of domination and plunder the riches of the land "just discoveries. " Anchored in mercantilism, Portugal will explore the wealth and develop a system of slavery marked out in the withdrawal of slave labor of African lands to their colonies in America. Later, it was aimed to understand how these kingdoms, and village communities will change with the process of colonial domination, leading to a process of constant economic and political crisis that will result in the failure of these organizations